Sorry, wrong number - How to separate fact from fiction in the information age. - Koomey, J.G.
Don't take figures for facts just because you see them in print. The author cites common misconceptions about the growth of Internet data and energy use associated with information technologies. He concludes that the misleading statistics mentioned here are just a few of many. Your best defense against being fooled by them is to think for yourself and do your homework. Never make important decisions based on "common knowledge" unless you can verify its accuracy independently. By thinking critically, you can be part of the solution rather than part of the problem.
Keywords: Internet data; United States; Accuracy; Common knowledge; Electricity; Energy use; Fact; Fiction; Information technologies; Misconceptions; Misleading statistics